The Exploration of Mathematics on Batik Trusmi - Rahmawati, Dwi; Noto, Muchamad Subali; Subroto, Toto; Amiruddin, Mohd. Hasril; Hafizatunnisa, Hafizatunnisa (Department of Mathematics, Universitas Negeri Padang (UNP), 2024)
The purpose of the literature review in this study was to thoroughly evaluate and assess the theories, signs, effects, and initiatives used to help students overcome their math anxieties. The type of research used is a literature study. This study used the systematic literature review (SLR) method. The data collection technique used is the inclusion criterion, and the data analysis technique used is exposition. Based on the findings of several studies, it is clear that mathematical anxiety negatively impacts students' learning outcomes, learning processes, and mathematical abilities, including their ability to solve math problems and other mathematical abilities. Of course, based on these studies, there is a need for efforts to overcome mathematics anxiety, both carried out by teachers and students so that the mathematics learning process can run smoothly. But not all math anxieties produce negativity. Some articles also mention that math anxiety can improve students' mathematical achievement.